2017
DOI: 10.1136/bjophthalmol-2017-310373
|View full text |Cite
|
Sign up to set email alerts
|

Ocular surface cytokine profile in chronic Stevens-Johnson syndrome and its response to mucous membrane grafting for lid margin keratinisation

Abstract: background To study the tear cytokine and the conjunctival and oral mucosal marker profile in chronic ocular Stevens-Johnson syndrome (SJS) and their alteration following mucous membrane grafting (MMG) for lid margin keratinisation (LMK). Methods In a 1-year prospective study, SJS cases (n=25) and age-matched/sex-matched healthy controls (n=25) were recruited. Tear specimen (Schirmer's strip), conjunctival and oral mucosal imprints were collected from controls and SJS cases pre-MMG and post-MMG (at first follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
44
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(50 citation statements)
references
References 25 publications
4
44
2
Order By: Relevance
“…In line with this hypothesis, Gurumurthy et al. () reported that tear levels of IL‐8 is up‐regulated not exclusively in the acute inflammatory phase but also in the persistently chronic inflammatory phase of ocular SJS, a condition characterized by scarring features.…”
Section: Discussionmentioning
confidence: 83%
See 4 more Smart Citations
“…In line with this hypothesis, Gurumurthy et al. () reported that tear levels of IL‐8 is up‐regulated not exclusively in the acute inflammatory phase but also in the persistently chronic inflammatory phase of ocular SJS, a condition characterized by scarring features.…”
Section: Discussionmentioning
confidence: 83%
“…) and it is a pro‐fibrotic factor by inducing epithelial‐to‐mesenchymal transition changes (Gurumurthy et al. ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations